Consumption of fish is not associated with risk of differentiated thyroid carcinoma in the European Prospective Investigation into Cancer and Nutrition (EPIC) study - Zamora-Ros, R; Castañeda, J; Rinaldi, S; Cayssials, V; Slimani, N; Weiderpass, E; Tsilidis, K; Boutron-Ruault, M; Overvad, K; Eriksen, A; Tjønneland, A; Kühn, T; et al. (American Society for Nutrition, 2017)
Background: Differentiated thyroid cancer (TC) is the most common endocrine cancer. Fish can be an important source of iodine and other micronutrients and contaminants that may affect the thyroid gland and TC risk.Objective: We prospectively evaluated the relations between the consumption of total fish and different fish types and shellfish and TC risk in the EPIC (European Prospective Investigation into Cancer and Nutrition) study.Methods: EPIC is a cohort of >500,000 men and women, mostly aged 35-70 y, who were recruited in 10 European countries. After a mean follow-up of 14 y, 748 primary differentiated TC cases were diagnosed; 666 were in women and 601 were papillary TC. Data on intakes of lean fish, fatty fish, fish products, and shellfish were collected by using country-specific validated dietary questionnaires at recruitment. Multivariable Cox regression was used to calculate HRs and 95% CIs adjusted for many potential confounders, including dietary and nondietary factors.Results: No significant association was observed between total fish consumption and differentiated TC risk for the highest compared with the lowest quartile (HR: 1.03; 95% CI: 0.81, 1.32; P-trend = 0.67). Likewise, no significant association was observed with the intake of any specific type of fish, fish product, or shellfish. No significant heterogeneity was found by TC subtype (papillary or follicular tumors), by sex, or between countries with low and high TC incidence.Conclusion: This large study shows that the intake of fish and shellfish was not associated with differentiated TC risk in Europe, a region in which iodine deficiency or excess is rare.